International Low Impact Development Conference 2015 2015
DOI: 10.1061/9780784479025.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Floating Treatment Wetlands for Nutrient Removal and Algal Toxin Control in Wet Detention Ponds

Abstract: Stormwater nutrient removal is a major contributor to the loadings in natural waterbodies, and any system not protected by the state or less than 10 acres, operate without water quality indefinitely. The permits do not require monitoring by private owners, but the effects are considered to be a contributor to the eutrophication of waterbodies across the world. Biomanipulation (biological mitigation) with the emerging technology, the Floating Treatment Wetland (FTW) can be used to remove nutrients, while preser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A comparison between the removal efficiencies presented in other studies on large-scale CFWs [5][6][7][8][9][10] and those revealed in this study is difficult due to the different treatment system designs, sampling procedures, and evaluation procedures used in the studies. This difficulty was also discussed by Headley & Tanner [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison between the removal efficiencies presented in other studies on large-scale CFWs [5][6][7][8][9][10] and those revealed in this study is difficult due to the different treatment system designs, sampling procedures, and evaluation procedures used in the studies. This difficulty was also discussed by Headley & Tanner [21].…”
Section: Discussionmentioning
confidence: 99%
“…A literature review identified six previous studies [5][6][7][8][9][10] which investigated the removal of total suspended solids (TSS) and nutrients from stormwater ponds by CFWs at seven different locations. All of the stormwater ponds investigated had a surface area of 100 m 2 or larger.…”
Section: Site Descriptionmentioning
confidence: 99%